Exploring factors influencing adherence to oral hygiene care among periodontal patients: a pilot study - Badiah, B; Kang, P.L; Hor, W.S; Razali, M; Dom, T.N.M (Universiti Kebangsaan Malaysia, 2013)
The objective of this study was to investigate in-depth factors influencing adherence to oral hygiene care among periodontal patients. This qualitative research was based on patients undergoing initial phase of periodontal therapy at the Universiti Kebangsaan Malaysia (UKM) Periodontic Clinics. The data collection were obtained using a focus group discussion (FGD) and the session was recorded and later transcribed for manual analysis. Six patients participated in the FGD. The main themes which emerged collectively from the discussion were ‘lack of knowledge’ and ‘poor motivation’ related to effective oral hygiene care. Respondents noted that motivation to adhere to oral hygiene care improved when clinicians undertook good professional care and when patients themselves experienced retrospective regret for their tooth loss. This study showed lack of oral health knowledge, poor attitude towards oral hygiene care, good dentist-patient relationship, regret about past neglect, cultural beliefs and affordability were the factors which might influence adherence to oral hygiene care among periodontal patients.